Development and characterization of microsatellite primers in the endangered Mediterranean shrub Ziziphus lotus (Rhamnaceae)1. (8th December 2016) - González‐Robles, Ana; Manzaneda, Antonio J.; Bastida, Jesús M.; Harvey, Nick; Jaime, Rafael; Salido, Teresa; Martínez, Luisa M.; Fernández‐Ocaña, Ana; Alcántara, Julio M.; Rey, Pedro J.
Abstract : Premise of the study: Microsatellite primers were developed to characterize and evaluate patterns of genetic diversity and structure in the endangered Mediterranean shrub Ziziphus lotus (Rhamnaceae). Methods and Results: Twenty microsatellite primers were developed for Z. lotus, of which 14 were polymorphic. We evaluated microsatellite polymorphism in 97 specimens from 18 Spanish and seven Moroccan populations. Between two and eight alleles were found per locus, and the average number of alleles was 5.54. Observed heterozygosity and expected heterozygosity ranged from 0.08 to 0.90 and from 0.08 to 0.82, respectively. Nine of these primers also amplified microsatellite loci in Z. jujuba . Conclusions: The microsatellite markers described here will be useful in studies on genetic variation, population genetic structure, and gene flow in the fragmented habitat of this species. These markers are a valuable resource for designing appropriate conservation measures for the species in the Mediterranean range.